Control System for U-Arm Robot Arm Movement with Linear Gripper Based on Inverse Kinematic Method - Prasetyo, Aditya Putra Perdana; Rahmatullah, Ikang; Exaudi, Kemahyanto; Rendyansyah, Rendyansyah (JITCE (Journal of Information Technology and Computer Engineering), 2024)
This research presents the development of a U-Arm model robot with three degrees of freedom, utilizing Inverse Kinematic calculations. The novelty of this project lies in its precise control of the robot arm's movements through advanced kinematic algorithms. Inverse Kinematics is a mathematical process used to determine the joint angles of the robot arm from known (x, y, z) coordinates of the end-effector and the lengths of each link. The robotic arm consists of four links with lengths of 8.2 cm, 15 cm, 16 cm, and 18.4 cm, respectively, and is equipped with a gripping module for object manipulation. The methodology involves calculating the joint angles required for the desired end-effector position, ensuring accurate and efficient movement. Testing results indicate an average coordinate error of 7.13%, demonstrating the system's precision and reliability. This error rate provides valuable insights into the performance and potential areas for improvement in the kinematic model. Additionally, this research includes the development of a program to control the servo motor speed using For and delay functions. This program enhances the robot's operational efficiency by allowing precise speed adjustments, which are crucial for various applications. Overall, this study contributes to the field of robotics by offering a detailed analysis of kinematic control and program development for a multi-link robotic arm, highlighting its potential for practical applications.